Demystifying AI and ML for Cyber–Threat Intelligence - Yang, Ming; Mohanty, Sachi Nandan; Satpathy, Suneeta; Hu, Shu (Information Systems Engineering and Management, 2025)
XI, 628 p. 190 illus., 143 illus. in color.